2019
DOI: 10.1007/978-3-030-24337-1_3
|View full text |Cite
|
Sign up to set email alerts
|

TextWorld: A Learning Environment for Text-Based Games

Abstract: We introduce TextWorld, a sandbox learning environment for the training and evaluation of RL agents on text-based games. TextWorld is a Python library that handles interactive playthrough of text games, as well as backend functions like state tracking and reward assignment. It comes with a curated list of games whose features and challenges we have analyzed. More significantly, it enables users to handcraft or automatically generate new games. Its generative mechanisms give precise control over the difficulty,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 26 publications
0
105
0
Order By: Relevance
“…A lot of research has focused on games that run on Infocom's Z-Machine game engine, an engine that can play a lot of the early, classic games. Recently, Microsoft has introduced the environment TextWorld to help create a standardized text adventure environment [25].…”
Section: G Text Adventure Gamesmentioning
confidence: 99%
“…A lot of research has focused on games that run on Infocom's Z-Machine game engine, an engine that can play a lot of the early, classic games. Recently, Microsoft has introduced the environment TextWorld to help create a standardized text adventure environment [25].…”
Section: G Text Adventure Gamesmentioning
confidence: 99%
“…The TextWorld framework (Côté et al 2018) supports procedural generation of parser-based IF games, allowing complexity and content of the generated games to be scaled to the difficulty needed for research. TextWorld domains have already proven suitable for reinforcement learning agents (Yuan et al 2018) which were shown to be capable of learning on a set of environments and then generalizing to unseen ones at test time.…”
Section: Related Workmentioning
confidence: 99%
“…TextWorld (Côté et al, 2018) is a text-based game where the agent interacts with the environment using short sentences. We generated a game composed of 3 rooms, 7 objects, and quest length of size 4.…”
Section: Textworld Environmentmentioning
confidence: 99%